Konsep Ilmu dan Akhlak dalam Pemikiran Ibnu Sina dan Ibnu Khaldun: Kontribusi bagi Pendidikan Islam - Hasan, Muflikhul; Abdurrahmansyah, Abdurrahmansyah; Sirozi, M.; Mahyudin, Edy (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the concepts of knowledge (‘ilm) and morality (akhlaq) in the thoughts of Ibn Sina and Ibn Khaldun, viewed from the aspect of their contribution to Islamic education. This research is a literature review, analyzing various conceptual information and both qualitative and quantitative data obtained from previous scholarly articles. The databases used to collect articles for this literature study include Google Scholar, DOAJ, ResearchGate, and ScienceDirect, which provide reliable and up-to-date academic sources. The data were analyzed using content analysis, by examining themes, concepts, and theoretical relevance to produce a comprehensive synthesis in accordance with the research focus. The findings and discussion reveal that the concepts of knowledge, ethics, and methods of contemporary Islamic education are greatly influenced by the works of Ibn Khaldun and Ibn Sina. Both rejected the notion of knowledge as merely technical, emphasizing instead its role in guiding humans toward truth, happiness, and morality. Ibn Khaldun highlighted knowledge as a cultural product and a tool for building civilization, with ethics rooted in social interaction. Conversely, Ibn Sina stressed the integration of reason and faith, gradual education, and the teacher as a moral role model. Their ideas are significant as they contribute to shaping the insan kamil a complete human being capable of competing globally while addressing the challenges of globalization through the integration of knowledge, faith, and ethics